Efficient one pot multi-component domino Aldol condensation–Michael addition–Suzuki coupling reaction for the highly functionalized quinolines. Issue 33 (12th August 2015) - Ubba, Eethamukkala; Kumar, Y. Suneel; Dasaradhan, C.; Khan, Fazlur-Rahman Nawaz; Jeong, Euh Duck; Chung, Eun Hyuk
Graphical abstract: Abstract: A parallel and advantageous multi-component one pot reaction has been developed utilizing domino Aldol condensation–Michael addition–Suzuki coupling approach for a variety of 2, 3-disubstituted highly functionalized quinolines. The domino reactions of 2-chloro-3-formylquinolines, 1 acetophenones, 2 and distinctive boronic acids, 3 were carried out utilizing PdCl2 (PPh3 )2 /tripotassium phosphate/ethanol–water system. At 80 °C they gave diversified functionalized quinolines in good yields.